PERANCANGAN DESAIN KALENDER CAKA BALI SEBAGAI MERCHANDISE OBJEK AGNI DENGAN PENDEKATAN NEO INDONESIANA - Prabawa, Widi; Dewi, Alit Kumala; Ida Ayu, Dwita Krisna Ari (Program Studi Desain Komunikasi Visual, 2025)
The Caka Bali Calendar is a cultural heritage rich in traditional and spiritual values but often perceived as complex and difficult to understand by the modern audience. To address this, the calendar was redesigned using the Neo-Indonesiana approach, combining traditional elements with contemporary design. This project focuses on simplifying calendar components such as tri wara, panca wara, full moon, new moon, and sasih, creating an accessible and user-friendly calendar for the younger generation. Employing cultural research and visual exploration methods, the project delivers a minimalist, aesthetic, and functional design. The creative process incorporates modern digital techniques with the philosophy of Cipta, Rasa, and Karsa, emphasizing a balance between tradition and innovation. This calendar serves not only as a time marker but also as a medium for cultural education and preservation.